DECORATIVE DECORATIONS OF OLD BUILDINGS - Fayzulla Chorshanbayev Ziyatovich (Research Focus International Scientific Journal, 2024)
This article explains that the correct selection of local building materials used in the repair of monument patterns and decorations is a necessary process. There are methods of special preparation of building materials used in the repair of architectural monuments of Uzbekistan and the order of their use.